Use of light-emitting diode (LED) in the physiology of cultivated plants – review - Lazzarini, Luiz Eduardo Santos; Pacheco, Fernanda Ventorim; Silva, Samia Torres; Coelho, Adriane Duarte; Medeiros, Ana Paula Ribeiro; Bertolucci, Suzan Kelly Vilela; Pinto, José Eduardo Brasil Pereira; Soares, Joyce Doria Rodrigues (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The objective of this study was to demonstrate the effects of the use of LED bulbs in the physiology of cultivated plants. Light-emitting diodes (LEDs) have been proposed as a light source for controlled environments or in plant growth chambers, since they have desirable characteristics for plant development. The development and physiology of plants are strongly influenced by the environment light spectrum provided by the LEDs, among which we can mention the blue, red, green, and their combinations. The blue light, for example, is responsible for a number of important photomorphogenetic features in plants, including stomatal control. Studies indicate that the red wavelength is efficiently absorbed by the pigments present in the plants, since its wavelength is very close to the absorption peak of chlorophyll. The relevance of green light responses is based on the assumption that there are situations in nature that the plant may find conditions of increased green radiation in its growing environment. LED bulbs offer many advantages as radiation sources for plants, but there are difficulties that delay their implementation for applications in the plant cultivation. With the advancement of technologies, the characteristics and performance of LED bulbs, as a source of radiation for plants, tend to be improved. However, this efficiency varies among the light spectra and the species. Thus, the advancement in the use of LEDs in the protected cultivation of cultivated plants is linked to specific physiological responses of each species.